THE CONCEPT OF WAR: LINGUISTIC OBJECTIFICATION IN GREEK MEDIATEXT (HIGHLI GHTING OF EVENTS IN UKRAINE, 2022–2024) - Roksolana Olishchuk; Khrystyna Kuybida (Іноземна філологія)
The research is dedicated to the analysis of linguistic representation of the concept of “war” in articles from the Greek media news platform CNN Greece for the period from February 2022 to February 2024 focusing on the topic of the Russian war in Ukraine. The conceptualized notion under investigation is examined based on linguistic objectifi cation means such as the central nomination of war – πόλεμος, and related units, including cognates and derivatives (πολεμικός, εμπόλεμος προπολεμικά πολεμάω), many of which are compounds (πολεμοφόδια, ανταρτοπόλεμος, καταπολέμηση, ψυχροπολεμικός). Regarding the fronts of military events in Ukraine, mention is made of the economic war and cyberwar (οικονομικός πόλεμος and κυβερνοπόλεμος, respectively). The synonyms of war are divided into two groups (επίθε-ση, εισβολή as a Russian invasion and μάχη, πάλη, αντεπίθεση as a struggle of Ukrainians). Among the antonyms, primary emphasis is placed on the lexeme νίκη. Syntactic combinations with linguistic units of diff erent lexical-grammatical classes (namely attributive, nominative, and predicative syntagms) and some stylistic phenomena (such as association, enumeration, periphrasis) are also considered as verbalizers of war. Figurative means, including epithets, metaphorical and metonymical combinations, are used in media texts to enhance the negative emotional impact of war. The analysis reveals that the war in Ukraine is illustrated in Greek media as aggressive and bloody. The concept of “war”, as demonstrated in the article, is characterized by complexity and multifaceted nominative fi eld in the examined media texts with a negative evaluative marking regarding the aggressor state. The linguistic representatives of the analyzed concept in Greek media texts play a crucial role in forming a negative attitude toward events in Ukraine for Greek readers, contributing to the creation and maintenance of the corresponding emotional mood.